The remarkable effect of alkali earth metal ion on the catalytic activity of OMS-2 for benzene oxidation. (July 2020) - Ni, Chunlan; Hou, Jingtao; Li, Lei; Li, Yuanzhi; Wang, Mingxia; Yin, Hui; Tan, Wenfeng
Abstract: Cryptomelane-type octahedral molecular sieve (OMS-2) is one of the most promising catalysts for VOCs oxidation, and introduction of metal ions in OMS-2 tunnel is widely used for tailoring its catalytic activity. Here, different types of alkali earth metal ions with the same X/Mn atomic ratio of approximately 0.012 (X represents Mg 2+, Ca 2+, and Sr 2+ ) were successfully introduced into OMS-2 tunnel by a one-step redox reaction. The catalytic test showed that introducing alkali earth metal ions into tunnels had a considerable effect on the catalytic performance of OMS-2 for benzene oxidation. The Sr 2+ doped OMS-2 catalyst exhibited the better catalytic activity compared with those of Mg-OMS-2 and Ca-OMS-2 samples, and was also superior to a commercial 0.5% Pt/Al2 O3 catalyst, as evidenced by its low reaction temperatures of T 50  = 200 °C and T 90  = 223 °C (corresponding to benzene conversions at 50% and 90%, respectively). The origin of the considerable effect of alkali earth metal doping on the catalytic activity of OMS-2 catalysts was experimentally and theoretically investigated by an 18 O2 isotopic labeling experiment, CO temperature-programmed reduction, O2 temperature-programmed oxidation, and density functional theory calculations. The greatest catalytic activity of Sr-OMS-2 compared with those of Mg-OMS-2 and Ca-OMS-2 samples was attributed to its highest lattice oxygen activity as well as its largest surface area. By introducing alkali earth metal ions into the OMS-2 tunnel, we developed a low-cost and highly efficient catalyst that could be used as alternative to noble metal catalysts. Graphical abstract: Image 1 Highlights: Mg 2+, Ca 2+, and Sr 2+ ions were successfully introduced into OMS-2 tunnel by a one-step redox reaction. The catalytic activity of alkali earth metal-doped OMS-2 for benzene oxidation was tested. Introducing alkali earth metal ions considerably affected the catalytic activity of OMS-2. Origin of alkali earth metal doping effect on benzene oxidation was experimentally and theoretically investigated. A low cost and highly efficient catalyst of Sr doped OMS-2 as an alternative to noble metal catalysts was obtained.